Inovasi Bahan Ajar PAI Dengan Model Problem Based Learning (PBL) Berbasis Budaya Lokal - Rolli Berutu; Hasrian Rudi Setiawan; Nurzannah Nurzannah (Jayapangus Press, 2025)
Learning in Islamic Religious Education (PAI) at the elementary school level continues to face challenges, particularly in instilling akhlaqul karimah (noble character values) in a way that is contextual and meaningful for students. A potential solution to address this issue is through the innovation of learning models that integrate Islamic values with local cultural wisdom found in students’ environments. This study aims to develop and validate an innovative learning model for PAI based on Problem-Based Learning (PBL), focused on the habituation of practicing akhlaqul karimah and Islamic manners through the integration of Batak and Pakpak cultural values in Dairi Regency. The research employed a Research and Development (R&D) design adapted from the Borg & Gall model, which was modified into seven stages. The developed learning model refers to the five main syntax components of PBL, namely: (1) orienting students to contextual problems, (2) organizing students for investigation, (3) guiding inquiry activities, (4) developing and presenting learning products, and (5) analyzing and evaluating the learning process. The validation results showed that the syntax model achieved a score of 90% (very valid), while the validation of the learning materials, such as student worksheets, reached 96% (very valid). The findings revealed that implementing a PBL model based on local culture is effective in enhancing students’ understanding of Islamic moral and ethical values, while also fostering tolerance, cooperation, and respect for diversity. Therefore, this innovative learning model is recommended for application in Islamic Religious Education (PAI) learning that emphasizes local cultural wisdom as a means to strengthen students’ character formation.